Destructive Thyroiditis: A Rare and Perplexing Complication of Lithium Therapy in Bipolar Disorder - Ni Wayan Saka Rahayu (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Lithium is a cornerstone therapy for Bipolar I Disorder, yet its use necessitates vigilant monitoring for adverse drug reactions (ADRs). While lithium-induced hypothyroidism is a well-documented complication, the emergence of thyrotoxicosis secondary to destructive thyroiditis is a rare and diagnostically challenging event. This report presents a systematic analysis of a case of suspected lithium-induced thyroiditis notable for its paradoxical clinical presentation as a severe depressive episode. Case presentation: A 33-year-old female with a 10-year history of Bipolar I Disorder, stable on lithium for two years, was admitted with a severe depressive episode and active suicidal ideation. The onset of her psychiatric decompensation was temporally correlated with a diagnosis of thyrotoxicosis (suppressed TSH <0.005 uIU/mL; elevated FT4 >7.77 ng/dL). A formal causality assessment using the Naranjo Adverse Drug Reaction Probability Scale yielded a score of 6, indicating a "probable" relationship between lithium and the thyroiditis. Critically, the thyrotoxic state, which conventionally mimics mania, presented atypically as severe depression. Conclusion: This case of probable lithium-induced destructive thyroiditis, presenting paradoxically with severe depression, underscores the critical need for a high index of suspicion for iatrogenic endocrinopathies in patients on lithium who exhibit any mood destabilization. A systematic approach to ADR assessment is essential to guide appropriate clinical management in such complex presentations.